Tensile behaviour of MWCNTs-modified epoxy grout for pipeline repair - Arifin, Hanis Hazirah; Zainal, Nurfarahin; Zardasti, Libriati; Yahaya, Nordin; Lim, Kar Sing; Lai, Jian Wey; Md Noor, Norhazilan (EDP Sciences, 2018)
Infill material in the pipeline repair system works by filling the gap that is usually caused by corrosion before the fibre wrapper can be applied for pipeline recovery. In this study, nanocomposites were prepared by adding a small amount of Multi-walled carbon nanotubes (MWCNT) to an existing commercial epoxy resin grout aiming to evaluate their behaviour regarding neat epoxy grout as infill material in composite repair for steel pipeline subjected to external metal loss. The dispersion of the nanoparticles in the epoxy resin has been conducted through ultrasonic and calendaring technique. The results of modified epoxy grout were compared to neat epoxy grout to identify if the MWCNTs are advantageous to existing materials. By comparing the results, 0.5% of MWCNT filler has significantly improved the strength by almost 53.3%. In addition, the results also indicate that MWCNT filler has increased the modulus of elasticity of the infill material. Furthermore, the morphologies image displayed that MWCNTs has been well merged into the matrix, and made the fracture cross section rougher through sharing the stress. Therefore, it demonstrated the intrinsic potential of the CNTs in modifying the properties of the composites.